2017
DOI: 10.17129/botsci.778
|View full text |Cite
|
Sign up to set email alerts
|

Copper-induced changes in nutrient uptake, enzymatic and non-enzymatic antioxidant systems in horehound ( Marrubium vulgare L.)

Abstract: , in a Cu 2+ concentration-dependent manner. The treatment with copper gives rise to positive effects on antioxidant enzymes activities (SOD and CAT enzymes) and to an increase of total phenol and flavonoid contents. Unexpectedly, no correlation with the anti-radical scavenging activity was observed. Conclusions: Marrubium vulgare possess an intrinsic capability to cope with the Cu stress by activation of the enzymatic and non-enzymatic antioxidant systems. Keywords: Marrubium vulgare L., copper, nutrient upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As a first screening, we performed the DPPH assay, commonly used to determine FRS activity of natural compounds [ 45 ]. Moreover, this assay can be helpful in lead-finding of novel antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…As a first screening, we performed the DPPH assay, commonly used to determine FRS activity of natural compounds [ 45 ]. Moreover, this assay can be helpful in lead-finding of novel antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…M. vulgare prefers alkaline soils [ 10 ]. Amri et al [ 11 ] reported that different concentrations of copper reduce the uptake and translocation of cationic elements Fe 2+ , K + , and Ca 2+ in a Cu 2+ concentration-dependent manner in the aboveground part of the plant. Treatment with copper stimulates antioxidant enzymes activities (superoxide dismutase (SOD) and catalase (CAT) enzymes) and increases the total phenolics (flavonoid) content.…”
Section: Botanical and Agronomical Featuresmentioning
confidence: 99%
“…Our results showed that raw materials originating from unstressed plant contained more marrubiin compared to leaves harvested from plants grown in stressed conditions. In detail, the plants were treated with CuSO 4 (80, 200 and 300 mg/L) for eight weeks according to the related literature . As highlighted in Figure , there are significant differences ( P < 0.05) in the amount of marrubiin, depending on the growth conditions.…”
Section: Resultsmentioning
confidence: 99%